Isolation and Identification of Ficus Palmata Leaves and Their Antimicrobial Activities (Journal of Scientific Research, 2017)
The aim of this work is to investigate functional compounds analysis and their antimicrobial activity of Ficus palmata leave. In this work some functional compounds were isolated by column chromatographic techniques and identification of their structure by spectroscopic (NMR, IR, Mass, UV, etc.) methods. Catechin, Genistein, ?-Sitosterol and Stigmasterol compounds were isolated. These compounds firstly were isolated from F. palmata leave. The antimicrobial activity of these compounds has been investigated with some different bacterial stains. In this study, it has been shown that zone of inhibition power activities of these compounds showed potent antimicrobial activity as compared to standard drug.